How Do Women Fare in Rural Non-Farm Economy? - Fuje, Habtamu (World Bank, Washington, DC, 2017)
This paper studies the gender-based differences in access to and return from economic activities in the rural non-farm economy (RNFE) using panel datasets from Uganda and Ethiopia. The results show that female-headed households have limited access to paid employment and self-employment in the sector, particularly in some industries. These households also earn lower returns from RNFE than male-headed households, and the gross return gap is much higher in Uganda than in Ethiopia. Furthermore, endowment differences do not explain the return gap in Ethiopia, and only partially explain the gap in Uganda.